Elemental Analysis of Brake Pad Using Natural Fibres. (2019) - Sri karthikeyan, S.; Balakrishnan, E.; Meganathan, S.; Balachander, M.; Ponshanmugakumar, A.
Abstract: Brakes have been advanced in the recent years through many developments. Previously all these years brake pads were made of asbestos fiber which are very harmful in many ways. When vehicles apply brake, the asbestos gets wear down and releases asbestos dust into the ambience and surrounding. This asbestos dust also gets entrapped inside the brake housing which is also a vital problem to be considered. Hence when there is requirement to open the brake housing, the asbestos dust is released into the air and the workers may accidentally inhale it without consciousness. It also posed a risk during manufacturing in industries as the workers are exposed to asbestos risk when they knowingly or unknowingly come into contact with asbestos. Thus a new development is introduced with certain natural fibers such as jute, KENAF and aloe vera along with additives such as epoxy resin and hardener. All these fibers are used to make brake pad material which posses certain properties and the results of various analysis done have been obtained to make a good use for manufacturing brake pads in the upcoming future.